Electronic structure of Gd based transition metal antimonides GdTSb (T = Ni, Pt) - Sahariya, Jagrati; Kumar, Pancham; Bhamu, K. C.; Soni, Amit (2nd International Conference on Condensed Matter and Applied Physics (ICC-2017), 2018)
We report the electronic and magnetic properties of ternary GdNiSb and GdPtSb compounds with cubic MgAgAs type structure. The energy bands, density of states and atom specific magnetic moments of compounds have been computed using GGA+U approach. The calculations predict that GdNiSb is a small band gap semiconductor whereas GdPtSb is metallic in nature.